Effects of Reflective Inquiry Teaching Method on Students’ Retention Ability in Domestic Installation Module in Technical Colleges of Yobe State, Nigeria - Dauda Moses (International Journal of Social Sciences & Educational Studies, 2020)
The aim of this study was to assess the effects of reflective inquiry teaching method on students’ retention ability in domestic installation module in technical colleges of Yobe State, Nigeria. In guiding the study, two research questions and two hypotheses were formulated in line with the specific objectives. A pretest – posttest nonequivalent control group quasi experimental research design was adopted for the study. Four intact classes from 4 technical colleges were selected to give a sample size of 88. Domestic Installation Retention Test (DIRT) was used to generate data for the study. The instrument was validated by three validates from the department of Electrical Technology Education, Modibbo Adama University of Technology, Yola. To determine the reliability of the instrument, Cronchbach Alpha reliability method was used and a reliability coefficient of 0.84 was obtained. Mean statistic was used to answer the two research questions of the study while the two null hypotheses of the study were tested using t-test and ANCOVA at 0.05 level of significance. Findings of the study revealed among others that reflective inquiry teaching method enhances retention abilities in students when used in teaching domestic installation. It further revealed that male and female students’ retention in domestic installation was high when taught using reflective inquiry teaching method. The study concluded that using reflective inquiry teaching method to teach students of electrical installation and maintenance works trade in Yobe State enhances the students’ retention ability which is visible in the retention test scores. The study recommended among others that teachers should employ reflective inquiry teaching method while engaging students in more work that will enable them develop critical thinking abilities.